The legal issues concerning Nigerian’s student education loan act: A lesson from Uganda perspective - Muwaffiq Jufri; Paul Atagamen Aidonojie; Erma Rusdiana; Godswill Owoche Antai; Eregbuonye Obieshi (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: Education is said to be one of the major keys to development and civilization. Concerning this, the Nigeria and the Uganda governments had sought to enhance and facilitate tuition fees of tertiary education of peasant citizens, by enacting the Student Loan Act, Unlike the Uganda Education Loan Act, there seems to be a gridlock in accessing education loans in Nigeria. Purpose/Study Objectives: In this regard, this study examines the issues concerning the Nigeria and Uganda tertiary education loan act, with a view of taking a leap from the Uganda student loan act in improving on the Nigeria student loan act. Design/Methodology/Approach: In this regard, the study adopts a hybrid study method, 406 questionnaires were sent to respondents residing in Nigeria and Uganda. The results obtained were analyzed using a descriptive and analytical method. Findings: The study identified significant flaws in the Nigeria Loan Act that risk undermining its intended purpose, whereas the Uganda Tertiary Education Loan Act offers a more effective framework, granting students better access to loans and scholarships. Consequently, the study concludes that Nigeria should adopt key aspects of Uganda’s model, particularly its student-friendly provisions, to improve access to educational financing. It therefore recommends that Nigerian policymakers reform the existing loan system by integrating successful elements from Uganda’s approach, ensuring greater equity and efficiency in supporting students’ academic pursuits. Paper Type: Research Article